Exploring the Stakeholders Salience for the adoption the Principles and Tools of Cleaner Production in Brazil Companies - Oliveira Neto, Geraldo Cardoso; Godinho Filho, Moacir; Ganga, Gilberto Miller Devós; Costa, Benny Kramer (Review of Business Management, 2015)
The objective of this study consists in identifying the environmental influences practiced by the stakeholders (government, economic agents and society), and understand the attributes used by these, regarding power, legitimacy and urgency to influence Brazilian companies on incorporating principles and tools of cleaner production. In particular, this research aims to establish a typology based on stakeholder Mitchell et al., (1997). The research method used was bibliographic research, bibliometric and the analysis of content for the selection of articles, which allowed the development of a structured questionnaire for an exploratory survey and multivariate data analysis through multiple correspondence analysis. The results indicate that the Brazilian government influences companies through regulatory power and legitimacy to strengthen environmental education. Economic agents in one group of companies adopted the power through the active participation of shareholders, while the other used definite influence, alerting about the possibility of obtaining economic and environmental advantage to become more economically inclusive for sustainable development. In one group of companies, the Brazilian society adopted legitimacy through changes in values and the spread of environmental performance. In another group, the power of legitimacy was used, denoting critical reorganization of aspects aimed at sustainability. It was identified that the urgency attribute, used by stakeholders, did not have influence on Brazilian companies. The stakeholders’ influence boosted companies with greater magnitude in principle and implementation of the cleaner production tool, to assess the material intensity for the control of waste destination in the production process.